FACTORS OF REINTEGRATION OF CHILDREN IN CONFLICT WITH LAW - Paul, Binoy; Paul, Victor (Journal of Dharma, 2020)
Building an ethical society involves lifelong learning and training, individually and collectively. On many occasions, crime and offence happen in the life of children. Juvenile Justice Act 2015 of India covers two categories of children: Children Need Care and Protection (CNCP) and Children in Conflict with Law (CCL). The behaviour of CCL is one of the most complex areas of behavioural science. Recidivism proves that the present reintegration is insufficient to arrest crime. This study focuses on the factors that support the reintegration of the CCL who had undergone the procedures of the Juvenile Justice Board (JJB). This is an exploratory study conducted in Kerala, India, to find the significant factors that contribute to successful reintegration, making children part of an ethical society. The methodology of the study is qualitative in nature and using data collected from boy offenders who have undergone the procedure of JJB and their parents and officials through different individual case studies. All children who participated in the survey have been rehabilitated, but reintegration seems yet to be completed.